A new species of Apertochrysa Tjeder, 1966 and new record of Plesiochrysa ramburi (Schneider, 1851) (Neuroptera: Chrysopidae) from China, with potential biocontrol significance - Wang, Maozhi; Li, Ziyuan; Liu, Xingyue (Zootaxa, 2023)
A new green lacewing species Apertochrysa roseusfrontata sp. nov. and a newly recorded Plesiochrysa ramburi (Schneider, 1851) (Neuroptera: Chrysopidae: Chrysopinae) from South China are described based on the morphological characters of both adults and larvae. Both species were found predating Dysmicoccus neobrevipes Beardsley, 1959 (Hemiptera: Pseudococcidae) on sisal (Agave sisalana Perrine, 1838) in Guangdong Province.